KREATIVITAS GURU DALAM PENGEMBANGAN SUMBER DAN METODE AJAR UNTUK PENCAPAIAN TUJUAN PENDIDIKAN AGAMA KRISTEN - Heryanto Heryanto (JURNAL PENELITIAN FISIKAWAN, 2019)
The education always requires teaching, but not all teaching is education. Educational cases are conceit of teachers who always have an important role n educational process. One assumption said that the teacher influences teaching and learning process. Therefore, the teacher should have a good ability and skill to teach. For this reason, it takes a professional teacher who is creative in teaching.